Analysis of Genetic Variations And Specific Locus of Banjar Hulu Tribe Through Short Tandem Repeat (STR) Locus Combine Dna Index System (Codis) in Nuclear DNA (Indian Journal of Forensic Medicine & Toxicology, 2020)
Based on the 2010 Indonesian Population Census, there are 1,300 ethnic categories with various sub-tribaldetails. Ethnic diversity is important in terms of identification, such as natural disasters, accidents, crime,and the discovery of unidentified corpses that may come from various tribes. Forensic Medicine viewsgenetic diversity and variation as one of the challenges in identification. Genetic variation and kinship inBanjar Hulu tribe have never been done.The aim of the study are identify and analyze the genetic variationof Banjar Hulu tribe through nucleus DNA examination of short tandem repeat (STR) Loci combined DNAindex system (CODIS). This study is a descriptive observational study that aims to explain the geneticvariation of Banjar Hulu tribe. The design of this study is cross-sectional. This study was conducted in twostages, the first stages is to obtain information on family tree from the study subjects conducted by interview.Then the second stage is to draw blood from the study subjects’ criteria. Blood is drawn from peripheralvein. Then, there will be DNA examination and analysis of genetic variation. Result of the study show THO1allele 9.3 locus, D3S1358 allele 12 locus, and D16S539 allele 12 locus, D8S1179 allele 12 locus are typicalmarker for Banjar Hulu tribe. Banjar Hulu tribe have specific loci and alleles.